(untitled) (Philology, 2023)
Translation in the field of humanities, which plays a key role in the evolution of ideas and thought on an international scale, is characterised by inherent specificities, and poses many difficulties. The article summarizes and exposes its particularities and carries an overview of its place in Bulgaria today, relying on statistical data, based on which it derives and analyses several trends. The subsequent analysis of the existing imbalances and some relatively unfavourable trends in the translation of humanities in Bulgaria takes into account the objective market circumstances, focuses more on the human factor and especially on the central figure of the translator, and points out as an important problem the practical lack of theory and criticism of the translation in the field of humanities. A multidisciplinary approach is suggested to support this highly specialised translation, as well as specific actions at all stages of the transfer of scientific knowledge through translation, with an explicit emphasis on translators’ training and the development of adequate criticism of translations. The practical implementation of this approach could form the basis of a long-term strategy to support and develop the translation in the field of humanities in Bulgaria. The article combines an analytical approach with an overview and programmatic presentation.